Utilising social networking services as a collective medium to support design communication in team collaboration. (21st September 2020) - Kim, Mi Jeong; Hwang, Yeon Sook; Hwang, Ha Sung
Abstract : Purpose: A variety of collaborative technologies have been developed to support design communication among members of design teams, and understanding the affordances of these technologies is critical to effective design collaboration. This research explores the potential of social networking as a collective medium that encourages design communication among student designers at the conceptual stage of design in a studio course. Design/methodology/approach: For one semester, the student participants used different social networking services to communicate with their team members, and the authors analysed how they collaborated when solving a given problem using the collaborative tools. Findings: The results show that various social networking platforms support students' communication of design and exploration of problems differently by affecting their clarification of ideas and information sharing. Collective discussion and online support are useful for framing problems and ideation in collaborative design. Originality/value: This research proposes that social networking services appropriate to the activities needed to be chosen and provided to enable design communication to promote students' active learning through team collaboration.